First evidence of lymphatic filariasis transmission interruption in Cameroon: Progress towards elimination. - Hugues C Nana-Djeunga (PLoS Neglected Tropical Diseases, 2017)
Lymphatic filariasis (LF) is among the 10 neglected tropical diseases targeted for control or elimination by 2020. For LF elimination, the World Health Organization (WHO) has proposed a comprehensive strategy including (i) interruption of LF transmission through large-scale annual treatment (or mass drug administration (MDA)) of all eligible individuals in endemic areas, and (ii) alleviation of LF-associated suffering through morbidity management and disability prevention. In Cameroon, once-yearly mass administration of ivermectin and albendazole has been implemented since 2008. The aim of this study was to assess progress towards the elimination goal, looking specifically at the impact of six rounds of MDA on LF transmission in northern Cameroon.The study was conducted in the North and Far North Regions of Cameroon. Five health districts that successfully completed six rounds of MDA (defined as achieving a treatment coverage ≥ 65% each year) and reported no positive results for Wuchereria bancrofti microfilariaemia during routine surveys following the fifth MDA were grouped into three evaluation units (EU) according to WHO criteria. LF transmission was assessed through a community-based transmission assessment survey (TAS) using an immunochromatographic test (ICT) for the detection of circulating filarial antigen (CFA) in children aged 5-8 years old.A total of 5292 children (male/female ratio 1.04) aged 5-8 years old were examined in 97 communities. Positive CFA results were observed in 2, 8 and 11 cases, with a CFA prevalence of 0.13% (95% CI: 0.04-0.46) in EU#1, 0.57% (95% CI: 0.32-1.02) in EU#2, and 0.45% (95% CI: 0.23-0.89) in EU#3.The positive CFA cases were below WHO defined critical cut-off thresholds for stopping treatment and suggest that transmission can no longer be sustained. Post-MDA surveillance activities should be organized to evaluate whether recrudescence can occur.